Comparative Analysis of Different Techniques Used for Root Canal Obturation and their Effects on Long Term Tooth Longevity - Kashif Adnan, Ali Tahir, Hafiz Mahmood Azam, Ashar Hussain, Hazrat Bilal, Qurrat-Ul-Ain Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Root canal obturation plays a critical role in determining the long-term success and survival of endodontically treated teeth. Various obturation techniques, including cold lateral condensation, warm vertical condensation, and carrier-based obturation, differ in their ability to provide optimal sealing, fracture resistance, and resistance to bacterial microleakage. This study compares the effectiveness of these techniques in terms of filling density, mechanical stability, and long-term tooth longevity. Objective: The objective of this study was to evaluate and compare different root canal obturation techniques based on their sealing ability, fracture resistance, void formation, bacterial leakage, and long-term survival rates to determine the most effective approach for ensuring tooth longevity. Methods: Present study was conducted at Muhammad Medical and Dental College Mirpurkhas. Duration of study was Sep 2022 to August 2023. This in vitro study utilized extracted human teeth, standardized in terms of canal preparation and divided into three groups: cold lateral condensation, warm vertical condensation, and carrier-based obturation. Micro-CT analysis, stereomicroscopy, and mechanical testing were employed to assess filling density, void formation, and fracture resistance. Bacterial leakage and microleakage tests were conducted over a 6- and 12-month period to evaluate long-term sealing efficiency. Statistical analysis was performed using ANOVA and post-hoc Tukey’s test to determine significant differences among the groups. Results: Carrier-based obturation demonstrated the highest mean filling density (94.1%), superior fracture resistance (428 N), and the least bacterial leakage (22.1%). Warm vertical condensation also performed well, with high density (91.7%) and reduced voids, whereas cold lateral condensation exhibited the lowest density (85.2%), highest void formation (8.1%), and highest bacterial leakage (47.2%). Long-term survival rates favored carrier-based obturation (87.6%), followed by warm vertical condensation (81.2%), while cold lateral condensation showed the lowest survival (68.5%). Conclusion: Carrier-based obturation exhibited superior sealing ability, fracture resistance, and long-term success, making it the preferred technique for improving tooth longevity. Warm vertical condensation provided promising results, while cold lateral condensation showed higher failure risks. The findings suggest that modern thermoplastic techniques should be prioritized in clinical practice to enhance the success of endodontic treatments. Further in vivo studies are recommended to validate these results under clinical conditions. Keywords: Root Canal Obturation,Tooth Longevity,Sealing Ability,Fracture Resistance